Genealogia do fora: o lugar da ficção de Hilda Hilst e Juliano Garcia Pessanha - Suelen Ariane Campiolo Trevizan (2022)
Among the different literary trends that coexist nowadays, there is one that is characterized by the transit between multiple areas of knowledge and by the radicalization of textual genres, leading to a problematization of the language. This lineage, similar to what Michel Foucault called “thought from the outside” and Maurice Blanchot called “neutral”, responds to the following crisis unleashed by modernity: as technocracy advances across the globe and the specialist gains the primacy of the speech, what is the role of literature? At least since Romanticism, the impotence of the literary word offers resistance to social overdetermination. In the field of philosophy, the Nietzschean revaluation also acts in this sense. In Brazil, two important points are the works of Hilda Hilst (1930-2004) and Juliano Garcia Pessanha (1962), writers who dialogue with the negativity, problematize it and, in addition, evoke an extensive web of authors critical to the modernity. Currently, with the waning of the revolutionary impetus of the 1960's and 1970's and the hegemony of utilitarianism, the negativity itself is being questioned. As they both are representative of this broader phenomenon, Hilst's and Pessanha's writing is more closely observed in this thesis, especially their prose texts. Different methodological procedures are used, starting with archival research and literary criticism, in order to summarize the fiction of the two authors, passing through comparativism to, only then, discuss the proposed theoretical problem. By investigating how the thought from the outside would have influenced a certain modern conception of literature and how it participates in the contemporary literary system, it is concluded that, despite its marginal role, it continues to exercise the relevant task of promoting the subtle look and the encounter in times of widespread isolation.